Breast Cancer Mortality Trends among Women in the State of Espirito Santo Between 1980 and 2007 - Felix, Janaina Daumas (2011)
Introduction: Cancer, in some countries, has assumed the leading cause of death among the population. Objective: This study aims to evaluate the trend of breast cancer mortality among women residing in the state of Espirito Santo, Brazil. Methods: Descriptive study of a temporal series of women deaths whose underlying cause of death was breast cancer, living in Espirito Santo, in the period between 1980 and 2007. Historical series were constructed and mortality rates for breast cancer were calculated. The direct method was used for the standardization of mortality rates, and the population census of IBGE-2000 was considered standard for the state. The equations for linear trend were obtained from the SPSS program, version 17.0. Results: During the study period, there were 2,736 deaths from breast cancer. The mortality rate for this period ranged from 3.41 to 10.99 per one hundred women. The results suggest that there is a trend in mortality from breast cancer over the study period (p =0.001with growth of 75.42%). All ages as from 30 years showed a trend towards statistically significant increased mortality (p =0.001). Growth percentages increased, according to the older age groups, with 48.4% aged 40 to 49 years, reaching 92.3% in the group ≥ 80 years. Conclusions: This study provided the temporal patterns of mortality from breast cancer among women in Espirito Santo and could detect an increasing trend, mainly among older women.